Time-resolved gain saturation dynamics in InGaN multi-quantum well structures - Kyhm, K; Smith, J; Taylor, R; Ryan, J; Arakawa, Y (2004)
Transient gain spectra were measured for an In0.02Ga 0.98N / In0.16Ga0.84N multiple quantum well using the variable stripe length method (VSLM) in combination with the ultrafast optical Kerr gate (OKG) technique. Gain dynamics were measured for a range of excitation lengths from short (50 μm) to long (350 μm) stripes with the sample under femtosecond photoexcitation. Analysis of the temporal behaviour of gain and chemical potential suggests that stimulated emission originates from a photoexcited electron-hole plasma at early times; at later times localized states dominate as the electron-hole plasma becomes exhausted. Gain reduction at early times is attributable to coupling of the electron-hole plasma with photons along the stripe, whilst localized states are less susceptible to gain saturation. © 2004 WILEY-VCH Verlag GmbH and Co. KGaA, Weinheim.